Impella Support for Acute Myocardial Infarction Complicated by Cardiogenic Shock: Matched-Pair IABP-SHOCK II Trial 30-Day Mortality Analysis. Issue 10 (5th March 2019) - Schrage, Benedikt; Ibrahim, Karim; Loehn, Tobias; Werner, Nikos; Sinning, Jan-Malte; Pappalardo, Federico; Pieri, Marina; Skurk, Carsten; Lauten, Alexander; Landmesser, Ulf; Westenfeld, Ralf; Horn, Patrick; et al.
Abstract : Background: Percutaneous mechanical circulatory support devices are increasingly used in acute myocardial infarction complicated by cardiogenic shock (AMI-CS), despite limited evidence for their effectiveness. The aim of this study was to evaluate outcomes associated with use of the Impella device compared with intra-aortic balloon pump (IABP) and medical treatment in patients with AMI-CS. Methods: Data of patients with AMI-CS treated with the Impella device at European tertiary care hospitals were collected retrospectively. All patients underwent early revascularization and received optimal medical treatment. Using IABP-SHOCK II (Intraaortic Balloon Pump in Cardiogenic Shock II) trial inclusion and exclusion criteria, 372 patients were identified and included in this analysis. These patients were matched to 600 patients from the IABP-SHOCK II trial. The following baseline criteria were used as matching parameters: age, sex, mechanical ventilation, ejection fraction, prior cardiopulmonary resuscitation, and lactate. Primary end point was 30-day all-cause mortality. Results: In total, 237 patients treated with an Impella could be matched to 237 patients from the IABP-SHOCK II trial. Baseline parameters were similarly distributed after matching. There was no significant difference in 30-day all-cause mortality (48.5% versus 46.4%, P =0.64). Severe or life-threatening bleeding (8.5% versus 3.0%, P <0.01) and peripheral vascular complications (9.8% versus 3.8%, P =0.01) occurred significantly more often in the Impella group. Limiting the analysis to IABP-treated patients as a control group did not change the results. Conclusions: In this retrospective analysis of patients with AMI-CS, the use of an Impella device was not associated with lower 30-day mortality compared with matched patients from the IABP-SHOCK II trial treated with an IABP or medical therapy. To further evaluate this, a large randomized trial is warranted to determine the effect of the Impella device on outcome in patients with AMI-CS. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT03313687. Abstract : Supplemental Digital Content is available in the text.